The Violence of Being. The Holocaust in the Philosophy of Emmanuel Levinas - Pollefeyt, Didier (Problemos, 2022)
This contribution shows how the Jewish philosopher Emmanuel Levinas has been confronted autobiographically with National-Socialism (1933-1945) and how his personal experience and the experience of the Jewish people under Hitlerism were translated in his philosophical understanding of ‘being’ as ‘il y a’ (in English: ‘there is’). The Holocaust provides a unique negative point of entry to understand Levinas’ ontological category which is as such not understandable since in the il y a, there is no longer a subject that stands before the objectivity of reality. On the contrary, the il y a is exactly the category that expresses a situation where the subject itself has no longer the ‘right’ to exist as such but still does not stop to exist. This violence of being is exactly what Hitlerism wanted to do in creating the Holocaust and submitting the Jewish people to it. This makes understandable how the whole philosophy of Levinas is an effort to overcome the il y a through a moral answer to the Holocaust.